2008
DOI: 10.1016/j.colsurfa.2008.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cholesterol on the structure of stratum corneum lipid model membrane

Abstract: a b s t r a c tThis study describes the influence of cholesterol on a model membrane consisting of four stratum corneum (SC) lipids in three different states at 32 and 85 • C. Using small-angle X-ray diffraction on multilamellar vesicles, the lamellar repeat distance, D, was determined. Small-angle neutron scattering on unilamellar vesicles was used to calculate the membrane thickness, average area of the membrane surface per molecule, average volume per molecule in the membrane, and membrane density. After th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 52 publications
1
21
0
Order By: Relevance
“…32,33 There are not many studies published aiming to investigate the effect of CHOL on the SC lipid organization systematically. 34 A few studies report on the phase behavior of CER containing lipid mixtures including CHOL. 34,35 These studies reveal that CHOL controls the miscibility of the CER containing lipid mixtures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…32,33 There are not many studies published aiming to investigate the effect of CHOL on the SC lipid organization systematically. 34 A few studies report on the phase behavior of CER containing lipid mixtures including CHOL. 34,35 These studies reveal that CHOL controls the miscibility of the CER containing lipid mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…34 A few studies report on the phase behavior of CER containing lipid mixtures including CHOL. 34,35 These studies reveal that CHOL controls the miscibility of the CER containing lipid mixtures. In previous studies, the phase behavior of lipid mixtures prepared from isolated human CERs or pig CERs in the presence of varying levels of CHOL has been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The fatty acid is significantly more mobile than the ceramide [9]. The role of the cholesterol allows fluidity for the lipid bilayer [37], and the cholesterol sulfate facilitates and stabilizes the formation of the lipid lamellae [38].…”
Section: Stratum Corneum Modelmentioning
confidence: 99%
“…[9][10][11] Despite the potential importance of the effect of composition on the permeability of the SC lipid membranes, majority of studies in this area have focused on the characterization of structural changes in the lipid membranes induced by different compositional changes. 4,7,8,[12][13][14][15][16][17] For example, using neutron diffraction, long-chained saturated fatty acids were observed to form a separate fatty-acid-rich phase in the SC lipid membrane. 13 Studies based on spectroscopy have shown that the presence of unsaturated fatty acids within the SC lipid membrane perturbs the crystalline structure and enhances the fluidity of the lipid membrane.…”
Section: Introductionmentioning
confidence: 99%